The influence of CO2 laser beam power output and scanning speed on surface roughness and colour changes of beech (Fagus sylvatica) - Gurau, Lidia; Petru, Adrian; Varodi, Anca; Timar, Maria Cristina (BioResources, 2017)
The literature provides very little information about engraving or decorating wood using a laser beam. No study was found that considers the surface roughness of wood after such treatments. This paper therefore aimed to find the influence of varying the laser power output and scanning speed of a CO2 laser beam on the surface roughness and colour of beech wood (Fagus sylvatica) for aesthetic applications such as decorative drawing. Laser power outputs from 5.6 to 6.8 W were tested in combination with scanning speeds from 100 to 500 mm/s. The surface roughness was assessed with a robust filter and by following measuring and evaluation recommendations from previous research to reduce the bias from the wood anatomy. The surface roughness measured by a series of roughness parameters (Ra, Rq, Rt, Rk, Rpk, Rvk) and total colour difference E increased with laser power and decreased with scanning speed. A good correlation was found between surface roughness and wood colour change. Such correlations can be useful for selecting the laser power-scanning speed combinations capable of giving the chosen colour change at a minimum surface roughness.
Keywords: Laser power; Laser scanning speed; Wood surface roughness; Wood colour change; Robust filtering; Roughness parameters